The Design and Construction of a Bulge Testing Device Platform for Human Skin Tissue Applications - Fischer, Dustin (Blast Impact and Survivability Research Unit, 2021)
Limited standard mechanical testing practises and stress-strain data are available for anisotropic human skin tissue in biaxial loading configurations to suitably represent skin in vivo. Inconsistencies in mechanical and physical properties in the literature due to numerous physiological factors have restricted development of biaxial testing equipment in laboratories to ad hoc research solutions having limited modifiability and parametric control. This project aims to develop a biaxial tensile testing device and testing platform which can be used in a research laboratory setting to provide a springboard to expediate mechanical skin tissue testing. The device can be easily reconfigured to accommodate a range of bulge pressures, while being driven via a 10bar compressed air supply. Based on simplified modelling of skin as an elastomer, mechanical and pneumatic resistivecapacitive pressure vessel models are developed. These are used respectively to initially specify a modifiable piston-cylinder bulge testing apparatus, and to design a customisable discrete proportional-integral closed-loop feedback pressurisation rate control system and software control environment. Pressure-time histories were successfully collected and stored on a dedicated computer for silicone sheet samples of 50mm diameter, as a surrogate for skin, that were tested using the platform to maximum pressures of about 200 kPa, at rates set between 2 20 kPa/s. The efficacy of the rate control system was affected by resolution of discrete pressurisation components that were used. The described platform is currently suitable for controlled and measured bulge pressurisation of elastomers. It is recommended to extend facility of the current platform by integrating 3D imaging and measurement technologies, to evaluate deformation of bulged anisotropic skin tissue and map inhomogeneous stress-strain fields for complex tensile stress-strain evaluations.